Pohřby zvířat v době bronzové. - Kyselová, Veronika (Jihočeská univerzita, 2013)
The content of this thesis is to clarify burying of animals in the Bronze Age. The first part includes also an overview of burials during the Bronze Age in the territory of the Czech Republic. In the second part, osteological material from the Northwest Bohemia was analysed.
Burial of animals in the Bronze Age.